From ‘infoxication’ to ‘infosaturation’, a theoretical overview of the cognitive and social effects of digital immersion - Dias, Patrícia (Ámbitos. Revista Internacional de Comunicación, 2019)
This paper explores the cognitive and relational effects of digital immersion. Drawing on previous work on ‘infoxication’, the information overload resulting from the empowerment provided by digital technologies to users, this paper suggests the notion of ‘infosaturation’ as a theoretical development. As digital technologies are undergoing a paradigmatic shift from user-centered to techno-centered, its effects are also changing. Individuals not only tend to look for information that reinforces their previous beliefs, but digital applications are increasingly suggesting contents and actions based on previous behavior and usage profiles. This results in the redundancy of both contents and social networks, i.e. ‘infosaturation’.